Ibuprofen-loaded chitosan–lipid nanoconjugate hydrogel with gum arabic: Green synthesis, characterisation, in vitro kinetics mechanistic release study and PGE2 production test - Mahmood, Syed; Almurisi, Samah Hamed; AL-japairai, Khater Ahmed Saeed; Hilles, Ayah Rebhi; Alelwani, Walla; Bannunah, Azzah M.; Alshammari, Farhan; Alheibshy, Fawaz (MDPI, 2021)
Ibuprofen is a well-known non-steroidal anti-inflammatory (NSAID) medicine that is often used to treat inflammation in general. When given orally, it produces gastrointestinal issues which lead to lower patient compliance. Ibuprofen transdermal administration improves both patient compliance and the efficacy of the drug. Nanoconjugation hydrogels were proposed as a controlled transdermal delivery tool for ibuprofen. Six formulations were prepared using different compositions including chitosan, lipids, gum arabic, and polyvinyl alcohol, through ionic interaction, maturation, and freeze–thaw methods. The formulations were characterised by size, drug conjugation efficiency, differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FTIR). Further analysis of optimised hydrogels was performed, including X-ray diffraction (XRD), rheology, gel fraction and swelling ability, in vitro drug release, and in vitro macrophage prostaglandin E2 (PGE2 ) production testing. The effects of ibuprofen’s electrostatic interaction with a lipid or polymer on the physicochemical and dissolution characterisation of ibuprofen hydrogels were evaluated. The results showed that the S3 (with lipid conjugation) hydrogel provided higher conjugation efficiency and prolonged drug release compared with the S6 hydrogel.